Modeling and Finite Element Evaluation of a Composite Blade for a Small-Scale Horizontal Axis Wind Turbine - Patidar, Lekhraj; Agrawal, Hitesh; K Mehta, Pradeep; Bansod, Nakul; Shrotriya, Abhishek; Patel, Devendra; Patel, Gourav (Journal of Neonatal Surgery, 2025)
Growing environmental concerns such as global warming and ozone layer depletion have accelerated the global shift toward renewable energy sources, with wind energy being a significant contributor. A wind turbine functions by converting the kinetic energy of wind into mechanical energy, and subsequently into electrical energy. The primary components of a wind turbine include the tower, rotor blades, hub, gear assembly, generator, braking system, pitch, and yaw control mechanisms. Among these, the rotor blade is a critical element as it endures dynamic loads during operation. Hence, its design, manufacturing, and maintenance demand careful attention. Traditionally, mechanical systems are tested before deployment; however, the advancement of computer-aided engineering tools has enabled efficient virtual testing, reducing the need for physical prototypes. This approach saves both development time and cost. In the present study, a small-scale horizontal axis wind turbine blade is modeled using Pro/ENGINEER (Pro-E) 5.0, and a finite element stress analysis is conducted using ANSYS Workbench 14.5. The analysis aims to evaluate the structural integrity of the blade under operational loads and to identify regions vulnerable to stress concentration or failure. Results indicate that the blade tip experiences maximum stress and directional deformation, highlighting the need to maintain an adequate clearance between the blade and the tower.